Child Health Booklet: experiences of professionals in primary health care - Gisele Nepomuceno de Andrade; Tércia Maria Ribeiro Lima Rezende; Anézia Moreira Faria Madeira (SciELO, 2014)
Objective: Understanding the experiences of health professionals in primary care with the Child Health Booklet in child health care. Method: A qualitative study with a phenomenological approach, in which participated nurses and doctors from six teams of the Family Health Strategy (FHS) in Belo Horizonte, MG. In total, were carried out 12 non-directive interviews, using two guiding questions. Results: A comprehensive analysis of the speeches enabled the construction of three categories that signal the experiences of the professionals with the booklet. The experiments revealed difficulties arising from the limitations of knowledge about the instrument; incomplete filling out of the booklet by many professionals that care for children; the daily confrontations of the process and the organization of work teams; disinterest of families with the instrument. Conclusion: The research points possible and necessary ways to improve the use of booklets as an instrument of full child health surveillance.